EFEKTIVITAS KOMUNIKASI KLINIK AGRIBISNIS DALAM MENDUKUNG KEGIATAN PENANGKARAN BENIH PADI SAWAH DI KECAMATAN WONOSARI - Niwayan Meinawati; Asda Rauf; Wawan Tolinggi (Agrinesia: Jurnal Ilmiah Agribisnis, 2018)
The effectiveness of agribusiness clinic communication is a success in achieving the goal of agribusiness discipline of agribusiness by looking at the level of knowledge and attitude change from farmers after communication. This study aims to analyze the factors that influence the effectiveness of agribusiness clinic communication in supporting the breeding of paddy field seeds in Wonosari District, to know the communication process in agribusiness clinic service, and to know the effectiveness of agribusiness clinic communication in supporting the breeding activity of paddy paddy seeds in kecamatan wonosari. The research method used in this research is survey with data analysis using binary logistic regression. The results of this study show the influence of the accuracy of media extension on communication effectiveness. Communication process at the time of planning, execution, evaluation of activity sah walks well, and communication that happened at agribusiness clinic in support of breeding activity of paddy rice seedlings good enough but not yet effective. This is indicated by the level of knowledge of farmers about seed breeding activities of rice paddy is quite good and there are still farmers who have not responded well the existence of this agribisnis clinic. agribusiness clinic is actually very useful for them in supporting the breeding activities of rice paddy seeds in Wonosari District but the communication process that occurs in it should still be improved.